Achieving 18.14% Efficiency of Ternary Organic Solar Cells with Alloyed Nonfullerene Acceptor. Issue 11 (24th September 2021) - Yu, Kuibao; Song, Wei; Li, Yafeng; Chen, Zhenyu; Ge, Jinfeng; Yang, Daobin; Zhang, Jianqi; Xie, Lin; Liu, Cuirong; Ge, Ziyi
Abstract : The ternary strategy is an effective method to improve the efficiency of organic solar cells (OSCs). Herein, high‐performance OSCs with over 18% efficiency using PM6 as donor and alloy‐like acceptor containing two highly structurally similar acceptors (Y6 and Y6‐1O) is obtained. The spectral overlap of Y6 and Y6‐1O can increase the collection of photons via enhancing the absorption in near infrared region, which is conducive to improve the short‐circuit current density ( J SC ). Meanwhile, beneficial electron transport channels are established by the construction of cascaded energy levels of Y6 and Y6‐1O in the ternary films. In addition, compared with Y6‐ and Y6‐1O‐based binary devices, enhanced charge mobility and suppressed charge recombination are observed in the optimal ternary OSCs, contributing to better performance. The improved performance of ternary devices based on the introduction of Y6‐1O is also attributed to the enhancement of photon capture and improved charge extraction as well as optimized blend morphology. A very promising ternary strategy is presented with two highly compatible acceptors to synergize the device performance in the development of high‐efficient OSCs. Abstract : The ternary strategy is an effective method to improve the efficiency of organic solar cells (OSCs) via simply incorporating a suitable third component. Herein, a high‐performance ternary solar cell with over 18% efficiency using PM6 as donor and alloy‐like acceptor containing two highly structurally similar acceptors (Y6 and Y6‐1O) is obtained.